Coupling of dephosphorylation and nuclear export of Smads in TGF-β signaling - Dai, Fangyan (2010)
In eukaryotes, regulation of signaling mediators/effectors in the nucleus is one of the principal mechanisms that govern duration and strength of signaling. Smads are a family of structurally related intracellular proteins that serve as signaling effectors for TGF-β and TGF-β-related proteins. Accumulating evidence demonstrate that Smads possess intrinsic nucleocytoplasmic shuttling capacity, which enables them to transmit TGF-β signals from cell membrane to nucleus. We recently identified two important steps in the termination of nuclear Smad signaling. The first step is initiated by a serine/threonine phosphatase PPM1A that dephosphorylates Smad2/3 in the nucleus, thereby shutting down signaling capacity of phosphorylated Smad2/3. The second step involves nuclear export of dephosphorylated Smad2/3 with the aid of nuclear protein RanBP3 to terminate Smad signaling. This chapter introduces methods for examining nuclear export of Smad2/3 in TGF-β signaling.